Exploring the Limits of Cell Adhesion under Shear Stress within Physiological Conditions and beyond on a Chip - Melanie E. M. Stamp; Anna M. Jötten; Patrick W. Kudella; Dominik Breyer; Florian G. Strobl; Thomas M. Geislinger; Achim Wixforth; Christoph Westerhausen (Diagnostics, 2016)
Cell adhesion processes are of ubiquitous importance for biomedical applications such as optimization of implant materials. Here, not only physiological conditions such as temperature or pH, but also topographical structures play crucial roles, as inflammatory reactions after surgery can diminish osseointegration. In this study, we systematically investigate cell adhesion under static, dynamic and physiologically relevant conditions employing a lab-on-a-chip system. We screen adhesion of the bone osteosarcoma cell line SaOs-2 on a titanium implant material for pH and temperature values in the physiological range and beyond, to explore the limits of cell adhesion, e.g., for feverish and acidic conditions. A detailed study of different surface roughness Rq gives insight into the correlation between the cells’ abilities to adhere and withstand shear flow and the topography of the substrates, finding a local optimum at Rq = 22 nm. We use shear stress induced by acoustic streaming to determine a measure for the ability of cell adhesion under an external force for various conditions. We find an optimum of cell adhesion for T = 37 °C and pH = 7.4 with decreasing cell adhesion outside the physiological range, especially for high T and low pH. We find constant detachment rates in the physiological regime, but this behavior tends to collapse at the limits of 41 °C and pH 4.